Episodic Venting of a Submarine Gas Seep on Geological Time Scales: Formosa Ridge, Northern South China Sea. Issue 9 (9th September 2022) - Kunath, Pascal; Crutchley, Gareth; Chi, Wu‐Cheng; Berndt, Christian; Liu, Char‐Shine; Elger, Judith; Klaeschen, Dirk; Bohrmann, Gerhard
Abstract: The Formosa Ridge cold seep is among the first documented active seeps on the northern South China Sea passive margin slope. Although this system has been the focus of scientific studies for decades, the geological factors controlling gas release are not well understood due to a lack of constraints of the subsurface structure and seepage history. Here, we use high‐resolution 3D seismic data to image stratigraphic and structural relationships associated with fluid expulsion, which provide spatio‐temporal constraints on the gas hydrate system at depth and methane seepage at modern and paleo seafloors. Gas has accumulated beneath the base of gas hydrate stability to a critical thickness, causing hydraulic fracturing, propagation of a vertical gas conduit, and morphological features (mounds) at paleo‐seafloor horizons. These mounds record multiple distinct gas migration episodes between 300, 000 and 127, 000 years ago, separated by periods of dormancy. Episodic seepage still seems to occur at the present day, as evidenced by two separate fronts of ascending gas imaged within the conduit. We propose that episodic seepage is associated with enhanced seafloor sedimentation. The increasing overburden leads to an increase in effective horizontal stress that exceeds the gas pressure at the top of the gas reservoir. As a result, the conduit closes off until the gas reservoir is replenished to a new (greater) critical thickness to reopen hydraulic fractures. Our results provide intricate detail of long‐term methane flux through sub‐seabed seep systems, which is important for assessing its impact on seafloor and ocean biogeochemistry. Plain Language Summary: Gas hydrates are ice‐like compounds that form in marine sediments. They can reduce the permeability of the sediments by clogging up the pore spaces, and influence how methane gas flows through sediments and then seeps out of the seafloor. Seepage of methane into the water column plays an important role in seafloor biology and ocean chemistry. In this study, we use 3D seismic imaging to investigate the subseafloor sediments of a ridge in the South China Sea where gas is currently seeping into the ocean. Our data show, in high detail, how gas migrates upward through the sediments due to the buoyancy of gas. Our data also reveal mound structures at certain depths beneath the seafloor. We interpret that these mounds represent distinct phases in the geological past where gas was seeping out of the seafloor. This indicates that gas seepage at this ridge has switched on and off (episodically) throughout geological time. We speculate that the episodic seepage is associated with rapid seafloor sedimentation, which changes pressure conditions beneath the seafloor. Our work improves the understanding of how gas seepage processes can change on geological timescales. Key Points: Gas has accumulated beneath the base of gas hydrate stability, causing vertical gas conduit formation and seabed mounds Mounds imaged within the conduit record episodic seepage between 300 and 127 kyrs ago Quiescence may be associated with enhanced seafloor sedimentation that increases effective stress at the top of the gas reservoir